2019
DOI: 10.1002/lsm.23132
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Antimicrobial Properties of 405 nm Light and the Corning® Light‐Diffusing Fiber Delivery System

Abstract: Background and ObjectivesHospital‐acquired infections (HAIs) and multidrug resistant bacteria pose a significant threat to the U.S. healthcare system. With a dearth of new antibiotic approvals, novel antimicrobial strategies are required to help solve this problem. Violet‐blue visible light (400–470 nm) has been shown to elicit strong antimicrobial effects toward many pathogens, including representatives of the ESKAPE bacterial pathogens, which have a high propensity to cause HAIs. However, phototherapeutic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…The in vitro antimicrobial features of flexible Corning®light-diffusing fiber (LDF) on ESKAPE and other relevant pathogens (S. epidermidis, Streptococcus pyogenes, C. albicans, and E. coli) were measured. The authors found that the LDF delivery of 405 nm violet-blue light had a significant antimicrobial activity towards a wide range of pathogens under diverse experimental conditions [140]. Regarding in vivo assays, the drug had efficacy in invasive candidiasis, aspergillosis, and pneumocystis.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 99%
“…The in vitro antimicrobial features of flexible Corning®light-diffusing fiber (LDF) on ESKAPE and other relevant pathogens (S. epidermidis, Streptococcus pyogenes, C. albicans, and E. coli) were measured. The authors found that the LDF delivery of 405 nm violet-blue light had a significant antimicrobial activity towards a wide range of pathogens under diverse experimental conditions [140]. Regarding in vivo assays, the drug had efficacy in invasive candidiasis, aspergillosis, and pneumocystis.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 99%
“…Endoscopically delivered light reduced gastric Helicobacter pylori infection ( Ganz et al, 2005 ), urinary tract infection could successfully be treated in a rat model ( Huang et al, 2018 ) and biofilm growth on catheter material was demonstrated to be reduced by the influence of irradiation ( Vollmerhausen et al, 2017 ). The development of a light diffusing fiber delivery system ( Shehatou et al, 2019 ), a minimally invasive ingestible capsule ( Romano et al, 2016 ), the investigation of a continuous surface disinfection of hospital rooms during the patient’s presence ( Maclean et al, 2013 ) and a whole range of different patents ( Ahmed et al, 2018 ), demonstrate simultaneously the emerging significance of light-based technologies and their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial photoinactivation with visible light represents a promising microbial inactivation strategy, with many advantages and various potential applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Violet light with a wavelength of around 405 nm seems to be especially effective [ 8 , 9 ], but also blue light around 450 nm exhibits antimicrobial properties [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%